CPUE, BIOLOGICAL AND CONDITION FACTOR OF KAWAKAWA (EUTHYNNUS AFFINIS) CAUGHT BY PURSE SEINE IN WEST SUMATRA - Maya Agustina; Ririk Kartika Sulistyaningsih (Research Center for Fisheries, 2022)
Kawakawa (Euthynnus affinis) is one of the important catches of small-scale fisheries in Indonesia. This species is included in the neritic tuna group that mostly utilized by using purse seine and gillnet. This research aims to investigate the Nominal CPUE, Length distribution, and condition factor of kawakawa. Data collection was conducted for 11 months from February to December 2019 in Aceh, Sibolga, and Bengkulu (FMA 572). A total of 1,622 specimens was collected, measured (cm FL) and weighted (kg). CPUE analysis shows the fluctuations in each month, with the highest CPUE value in August and the lowest in May. The measurements showed that the length ranged from 20 – 55 cm FL and weight ranged from 0,13 – 3,06 kg. Analysis of length-weight relationships was W=0,00001FL3,1079 with a determination coefficient (R2) 0.967. The growth pattern of positive allometric. The highest relative condition factor (Kn) occurred at the upper limit of length class 21 cm FL with a value of 1.25 and the lowest at 57 cm FL with 1.06. The monthly relative condition factor tends to stabilise, with the highest value in December at 1.265 and the lowest in April at 1.081 and tended to fluctuated for the small-sized group. At the same time, adult fish tends to decrease along with the length increase.